Preparation method of mulberry twig composite phase change material capable of realizing self-regulation and heat management function
By using mulberry branches to prepare the impregnation treatment of porous fiber skeletons and phase change materials, the problem of insufficient heat storage and release ability of wood-based composite phase change materials is solved, and self-regulated thermal management function and efficient heat storage and release are achieved.
Patent Information
- Application Number
- CN202411703313.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-26
- Publication Date
- 2025-02-25
AI Technical Summary
The existing wood-based composite phase change materials have weak heat storage and release capabilities, and the natural defects and poor thermal properties of wood limit their further development.
Mulberry branches are used as raw material, and self-regulated thermal management function mulberry branches composite phase change material is prepared through the preparation of porous fiber frameworks and the impregnation treatment of phase change materials. The method includes placing mulberry branches in a solution of sodium chlorite and sodium hydroxide for heating reaction, followed by vacuum impregnation in a mixture of paraffin and copper oxide, and finally drying to obtain an optimized composite material.
The thermal management function of self-regulation is realized, the heat storage and release capacity and heat utilization rate are improved, and the temperature is optimized when the ambient temperature changes, energy saving and somatosensory comfort are improved.
Smart Images

Figure CN119505824A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of agricultural waste-based composite phase change materials. Background Art
[0002] In recent years, the depletion of non-renewable resources such as fossil energy has caused climate change and energy shortages. In order to solve this problem, people have continuously increased the development of renewable energy such as solar energy, wind energy, and tidal energy. However, the intermittent, uncertain, and high-cost characteristics of renewable energy have limited its further development. At present, phase change energy storage materials can store and release energy through physical phase changes, and the storage and release of energy are more stable. Traditional phase change energy storage materials have uniform temperature distribution and lack complete shape stability. In order to solve this problem, biomass was introduced as a porous support material.
[0003] Wood is a green and renewable biomass. Its anisotropic porous structure and excellent mechanical strength make it show certain potential in supporting phase change materials, which are used in furniture, houses, decorations and various functional materials. However, the natural defects of poor connectivity between wood cells and the functional weaknesses of poor thermal performance lead to the weak heat storage and release capacity of composite phase change materials. In addition, excessive logging will lead to an intensified greenhouse effect, which limits the further development of wood-based composite phase change materials. Therefore, the preparation strategy based on agricultural waste to enhance the connectivity of wood structure and improve the thermal management function is of great significance to promote the technology of wood-based composite phase change materials. Summary of the invention
[0004] The present invention aims to solve the problem that the existing wood-based materials as the supporting structure of phase change materials have weak heat storage and release capabilities, and further provide a method for preparing a mulberry branch composite phase change material with a self-regulating thermal management function.
[0005] A method for preparing a mulberry branch composite phase change material capable of realizing self-regulating thermal management function is carried out according to the following steps:
[0006] 1. Preparation of porous fiber skeleton:
[0007] The mulberry branches are placed in a sodium chlorite solution, heated at a temperature of 85°C to 100°C for reaction, then washed, and then placed in a sodium hydroxide solution, heated at a temperature of 75°C to 95°C for reaction, and finally washed, frozen and freeze-dried in sequence to obtain a porous fiber skeleton;
[0008] 2. Preparation of phase change materials:
[0009] The porous fiber skeleton is placed in a mixture of paraffin and copper oxide for vacuum impregnation, then taken out and heated for reaction, and finally dried to obtain a self-regulating thermal management function mulberry branch composite phase change material.
[0010] The beneficial effects of the present invention are:
[0011] 1. The present invention can use different kinds of mulberry branches as raw materials, such as mulberry and silkworm mulberry, which are natural and degradable biomass materials. As a substitute for whole wood, it can not only realize waste utilization, but also reduce the felling of mature wood. Using mulberry branches to develop a composite phase change material with excellent thermal management function is a new way to high-value utilization of agricultural solid waste.
[0012] 2. The maximum temperature of the mulberry branch is 64°C, while the temperature of the self-regulating thermal management function mulberry branch composite phase change material prepared by the present invention can reach 71°C, which can store more heat. It is a new type of agricultural waste-based composite phase change material that can achieve efficient heat storage and release. When the ambient temperature changes, the wood part of the self-regulating thermal management function mulberry branch composite phase change material responds first, and the skin and pith assist in self-regulation to achieve mutual temperature compensation, save energy, and improve body comfort.
[0013] 3. The self-regulating thermal management functional mulberry branch composite phase change material prepared by the present invention has good shape stability and excellent thermal properties, strong heat storage and release capacity, and high thermal utilization rate. It can be widely used in building energy-saving enclosure materials, heat storage and release functional accessories, etc.
[0014] 4. The raw materials of the present invention are abundant and easy to obtain, simple to prepare, low in investment cost, mild in reaction conditions, can be used for large-scale industrial production and processing, and have broad application prospects.
[0015] Attached Notes
[0016] Figure 1 This is an optical microscope photo of the mulberry branch raw material in step 1 of Example 1, a is pith, b is xylem, and c is bark;
[0017] Figure 2 This is a scanning electron microscope photograph of the woody part of the mulberry branch raw material in step 1 of Example 1;
[0018] Figure 3 This is a scanning electron microscope photograph of the wood part of the porous fiber skeleton prepared in step 1 of Example 1;
[0019] Figure 4 This is a scanning electron microscope photograph of the pith of the mulberry branch raw material in step 1 of Example 1;
[0020] Figure 5 This is a scanning electron microscope photograph of the medulla of the porous fiber skeleton prepared in step 1 of Example 1;
[0021] Figure 6This is a thermal imaging image of the self-regulating thermal management function mulberry branch composite phase change material prepared in step 2 of Example 1, where a is the pith, b is the xylem, and c is the bark;
[0022] Figure 7 This is the temperature-time curve of the mulberry branch raw material in step 1 of Example 1 and the self-regulating thermal management function mulberry branch composite phase change material prepared in step 2 under a cooling environment, where a is the mulberry branch and b is the self-regulating thermal management function mulberry branch composite phase change material. DETAILED DESCRIPTION
[0023] Specific implementation method 1: This implementation method is a method for preparing a mulberry branch composite phase change material capable of achieving self-regulating thermal management function, which is carried out in the following steps:
[0024] 1. Preparation of porous fiber skeleton:
[0025] The mulberry branches are placed in a sodium chlorite solution, heated at a temperature of 85°C to 100°C for reaction, then washed, and then placed in a sodium hydroxide solution, heated at a temperature of 75°C to 95°C for reaction, and finally washed, frozen and freeze-dried in sequence to obtain a porous fiber skeleton;
[0026] 2. Preparation of phase change materials:
[0027] The porous fiber skeleton is placed in a mixture of paraffin and copper oxide for vacuum impregnation, then taken out and heated for reaction, and finally dried to obtain a self-regulating thermal management function mulberry branch composite phase change material.
[0028] The beneficial effects of this embodiment are:
[0029] 1. This embodiment can use different types of mulberry branches as raw materials, such as mulberry and silkworm mulberry, which is a natural and degradable biomass material. As a substitute for whole wood, it can not only realize waste utilization, but also reduce the felling of mature wood. Using mulberry branches to develop a composite phase change material with excellent thermal management function is a new way to high-value utilization of agricultural solid waste.
[0030] 2. The maximum temperature of the mulberry branch is 64°C, while the temperature of the self-regulating thermal management function mulberry branch composite phase change material prepared in this embodiment can reach 71°C, which can store more heat. It is a new type of agricultural waste-based composite phase change material that can achieve efficient heat storage and release. When the ambient temperature changes, the wood part of the self-regulating thermal management function mulberry branch composite phase change material responds first, and the skin and pith assist in self-regulation to achieve mutual temperature compensation, save energy, and improve body comfort.
[0031] 3. The self-regulating thermal management functional mulberry branch composite phase change material prepared in this embodiment has good shape stability and excellent thermal properties, strong heat storage and release capacity, and high thermal utilization rate. It can be widely used in building energy-saving enclosure materials, heat storage and release functional accessories, etc.
[0032] 4. The raw materials of this embodiment are abundant and easy to obtain, the preparation is simple, the investment cost is low, the reaction conditions are mild, and large-scale industrial production and processing can be achieved, which has broad application prospects.
[0033] Specific implementation method 2: This implementation method is different from specific implementation method 1 in that the mulberry branches described in step 1 are in segments with a length of 1 cm to 1.5 cm and are dried to a constant weight. The rest is the same as specific implementation method 1.
[0034] Specific implementation method three: This implementation method is different from specific implementation method one or two in that: the volume ratio of the mass of the mulberry branch described in step one to the sodium chlorite solution is 1g (8-15) mL; the mass percentage of the sodium chlorite solution described in step one is 1%-3%, and the pH is 3-5. Others are the same as specific implementation method one or two.
[0035] Specific implementation method 4: This implementation method is different from specific implementation methods 1 to 3 in that: the volume ratio of the mass of the mulberry branch described in step 1 to the sodium hydroxide solution is 1g (8-15) mL; the mass percentage of the sodium hydroxide solution described in step 1 is 7% to 9%. Other aspects are the same as specific implementation methods 1 to 3.
[0036] Specific embodiment 5: This embodiment is different from specific embodiments 1 to 4 in that: in step 1, the mulberry branches are placed in a sodium chlorite solution, heated at a temperature of 85°C to 100°C for 5h to 7h, then washed, and then placed in a sodium hydroxide solution, heated at a temperature of 75°C to 95°C for 7h to 9h. The rest is the same as specific embodiments 1 to 4.
[0037] Specific implementation example 6: This implementation example is different from specific implementation examples 1 to 5 in that the freezing described in step 1 is performed at a temperature of -20°C to 0°C for 11 to 13 hours. The rest is the same as specific implementation examples 1 to 5.
[0038] Specific embodiment 7: This embodiment is different from Specific embodiments 1 to 6 in that the freeze drying in step 1 is carried out at a temperature of -70°C to -50°C for 20h to 30h. The rest is the same as Specific embodiments 1 to 6.
[0039] Specific embodiment eight: This embodiment differs from specific embodiments one to seven in that: the paraffin wax and copper oxide mixed solution described in step two is specifically prepared according to the following steps: the paraffin wax is heated to 65°C to 85°C, and maintained at a temperature of 65°C to 85°C for 0.5h to 1.5h, and then copper oxide is added and stirred for 0.5h to 1.5h at a speed of 6000r / h to 12000r / h and a temperature of 65°C to 85°C; the mass percentage of paraffin wax in the paraffin wax and copper oxide mixed solution is 98% to 99.5%. The rest is the same as specific embodiments one to seven.
[0040] Specific embodiment 9: This embodiment is different from specific embodiments 1 to 8 in that: the vacuum impregnation described in step 2 is specifically carried out according to the following steps: ① keep 3min to 10min under the pressure of -0.005MPa to -0.015MPa, and then keep 3min to 10min under the pressure of 0.005MPa to 0.015MPa; ② repeat step ① 2 to 5 times; the heating reaction described in step 2 is specifically carried out at a temperature of 70℃ to 90℃ for 1h to 3h. The rest is the same as specific embodiments 1 to 8.
[0041] Specific embodiment 10: This embodiment differs from specific embodiments 1 to 9 in that the drying described in step 2 is carried out at a temperature of 50° C. to 70° C. for 10 to 20 hours. The rest is the same as specific embodiments 1 to 9.
[0042] The following examples are used to verify the beneficial effects of the present invention:
[0043] Embodiment 1:
[0044] A method for preparing a mulberry branch composite phase change material capable of realizing self-regulating thermal management function is carried out according to the following steps:
[0045] 1. Preparation of porous fiber skeleton:
[0046] 2 g of mulberry branches were placed in 20 mL of sodium chlorite solution, heated at 95 ° C for 6 h, then washed with deionized water, placed in 20 mL of sodium hydroxide solution, heated at 80 ° C for 8 h, then washed with deionized water 3 times, frozen at -18 ° C for 12 h, and finally freeze-dried at -60 ° C for 24 h to obtain a porous fiber skeleton;
[0047] The mulberry branches are mulberry branches that are periodically cut down in the sericulture industry, in the form of segments with a length of 1 cm, and are dried to a constant weight at a temperature of 60° C.;
[0048] The mass percentage of the sodium chlorite solution is 2%, and the pH value is 4.6;
[0049] The mass percentage of the sodium hydroxide solution is 8%;
[0050] 2. Preparation of phase change materials:
[0051] The porous fiber skeleton was placed in a mixture of paraffin and copper oxide for vacuum impregnation, then taken out and reacted at 80°C for 2 hours, and finally dried at 60°C for 12 hours to obtain a self-regulating thermal management function mulberry branch composite phase change material;
[0052] The vacuum impregnation is specifically carried out according to the following steps: ① keep the pressure at -0.01MPa for 5 minutes, and then keep the pressure at 0.01MPa for 5 minutes; ② repeat step ① 3 times;
[0053] The paraffin wax and copper oxide mixed solution described in step 2 is specifically prepared according to the following steps: heating the paraffin wax to 80°C and maintaining the temperature at 80°C for 0.5h, then adding copper oxide to the paraffin wax at a speed of 9000r / h and a temperature of 80°C and stirring for 1h; the concentration of paraffin wax in the paraffin wax and copper oxide mixed solution is 98.8%, and the remainder is copper oxide.
[0054] Comparative experiment: The difference between this comparative experiment and Example 1 is that the use of copper oxide is eliminated in step 2. The rest is the same as Example 1.
[0055] Figure 1 This is an optical microscope photograph of the mulberry branch raw material in step 1 of Example 1, where a is pith, b is xylem, and c is bark. As can be seen from the figure, the mulberry branch has a three-layer porous structure of pith, xylem and bark.
[0056] Figure 2 This is a scanning electron microscope photograph of the woody part of the mulberry branch raw material in step 1 of Example 1; as can be seen from the figure, the woody part of the mulberry branch has a dense gap structure.
[0057] Figure 3 This is a scanning electron microscope photograph of the xylem in the porous fiber skeleton prepared in step 1 of Example 1; as can be seen from the figure, the cell gap of the mulberry branch xylem is increased after treatment (the gap is increased by 0.1μm to 2μm).
[0058] Figure 4 This is a scanning electron microscope photograph of the pith of the mulberry branch raw material in step 1 of Example 1; as can be seen from the figure, the pith of the mulberry branch has a uniform and smooth structure.
[0059] Figure 5This is a scanning electron microscope photograph of the pith of the porous fibrous skeleton prepared in step 1 of Example 1; as can be seen from the figure, after the mulberry branch is processed, circular holes (pore diameter is 0.5μm to 2.5μm) are created on the cell wall, which increases the connection between cells, thereby obtaining a porous fibrous skeleton with increased connectivity.
[0060] The self-regulating thermal management function mulberry branch composite phase change material prepared in step 2 of Example 1 was placed in an oven, and the oven temperature was raised from room temperature 30°C to 100°C. When the sample temperature was constant, the temperatures of three parts of the sample were observed; Figure 6 This is the thermal imaging image of the self-regulating thermal management function mulberry branch composite phase change material prepared in step 2 of Example 1, a is the pith, b is the xylem, and c is the bark; it can be seen from the figure that the temperature of the xylem (76.4°C) is higher than the bark (73.9°C) and pith (70.4°C), indicating that the mulberry branch composite phase change material has a three-layer temperature uneven structure. When the ambient temperature changes, the xylem in the mulberry branch composite phase change material responds first, and the bark and pith assist in self-regulation to achieve mutual temperature compensation.
[0061] Take the sample out of the 100℃ oven and place it at room temperature (30℃) to cool down; Figure 7 The temperature-time curve of the mulberry branch raw material in step 1 of Example 1 and the self-adjusting thermal management function mulberry branch composite phase change material prepared in step 2 under a cooling environment, a is mulberry branch, b is the self-adjusting thermal management function mulberry branch composite phase change material; it can be seen from the figure that when the sample is placed from high temperature to room temperature, the temperature of the untreated mulberry branch drops rapidly (1.75°C / min), while the mulberry branch composite phase change material prepared in the embodiment achieves mutual temperature compensation due to self-adjustment, and the temperature drops slowly (0.64°C / min), indicating that the mulberry branch composite phase change material has excellent thermal management capabilities. And the reason why the starting temperatures of the two curves in the figure are different is that the temperature of the mulberry branch a curve can reach a maximum of 64°C when it is stable, while the temperature of the self-adjusting thermal management function mulberry branch composite phase change material b curve reaches 71°C before it is stable.
[0062] The self-regulating thermal management function mulberry branch composite phase change material prepared in step 2 of Example 1 was subjected to DSC test. The test results showed that the melting enthalpy of the self-regulating thermal management function mulberry branch composite phase change material was 110.37 J·g -1 , indicating that it has large latent heat, suitable phase change temperature and excellent thermal stability, which is conducive to heat storage.
[0063] In the comparative experiment, the mulberry branch composite phase change material without copper oxide had a heating rate of 4.6°C / min and a heat storage effect of 105.11 J·g -1 After adding copper oxide, the heating rate of the mulberry branch composite phase change material in Example 1 increased to 5°C / min, the heat storage capacity was enhanced, and the melting enthalpy was 110.37 J·g-1 , reduce heat loss and keep the internal temperature stable.
Claims
1. A method for preparing a mulberry branch composite phase change material capable of achieving self-regulating thermal management function, characterized in that It is carried out in the following steps:
1. Preparation of porous fiber skeleton: The mulberry branches are placed in a sodium chlorite solution, heated at a temperature of 85°C to 100°C for reaction, then washed, and then placed in a sodium hydroxide solution, heated at a temperature of 75°C to 95°C for reaction, and finally washed, frozen and freeze-dried in sequence to obtain a porous fiber skeleton; 2. Preparation of phase change materials: The porous fiber skeleton is placed in a mixture of paraffin and copper oxide for vacuum impregnation, then taken out and heated for reaction, and finally dried to obtain a self-regulating thermal management function mulberry branch composite phase change material.
2. The method for preparing a mulberry branch composite phase change material capable of achieving self-regulating thermal management function according to claim 1, characterized in that The mulberry branches described in step 1 are in segments with a length of 1 cm to 1.5 cm and are dried to a constant weight.
3. The method for preparing a mulberry branch composite phase change material capable of achieving self-regulating thermal management function according to claim 1, characterized in that The volume ratio of the mass of the mulberry branch described in step one to the sodium chlorite solution is 1g (8-15) mL; the mass percentage of the sodium chlorite solution described in step one is 1%-3%, and the pH is 3-5.
4. The method for preparing a mulberry branch composite phase change material capable of achieving self-regulating thermal management function according to claim 1, characterized in that The volume ratio of the mass of the mulberry branch described in step one to the sodium hydroxide solution is 1g (8-15) mL; the mass percentage of the sodium hydroxide solution described in step one is 7%-9%.
5. The method for preparing a mulberry branch composite phase change material capable of achieving self-regulating thermal management function according to claim 1, characterized in that In step 1, the mulberry branches are placed in a sodium chlorite solution, heated at a temperature of 85° C. to 100° C. for reaction for 5 h to 7 h, then washed, and then placed in a sodium hydroxide solution, heated at a temperature of 75° C. to 95° C. for reaction for 7 h to 9 h.
6. The method for preparing a mulberry branch composite phase change material capable of achieving self-regulating thermal management function according to claim 1, characterized in that The freezing described in step 1 is specifically freezing at a temperature of -20°C to 0°C for 11h to 13h.
7. The method for preparing a mulberry branch composite phase change material capable of achieving self-regulating thermal management function according to claim 1, characterized in that The freeze-drying described in step 1 is specifically freeze-drying at a temperature of -70°C to -50°C for 20h to 30h.
8. The method for preparing a mulberry branch composite phase change material capable of achieving self-regulating thermal management function according to claim 1, characterized in that The paraffin wax and copper oxide mixed solution described in step 2 is specifically prepared according to the following steps: heating the paraffin wax to 65°C to 85°C and maintaining the temperature at 65°C to 85°C for 0.5h to 1.5h, then adding copper oxide and stirring for 0.5h to 1.5h at a speed of 6000r / h to 12000r / h and a temperature of 65°C to 85°C; the mass percentage of paraffin wax in the paraffin wax and copper oxide mixed solution is 98% to 99.5%.
9. The method for preparing a mulberry branch composite phase change material capable of realizing self-regulating thermal management function according to claim 1, characterized in that The vacuum impregnation described in step 2 is specifically carried out according to the following steps: ① maintain for 3min to 10min under a pressure of -0.005MPa to -0.015MPa, and then maintain for 3min to 10min under a pressure of 0.005MPa to 0.015MPa; ② repeat step ① 2 to 5 times; the heating reaction described in step 2 is specifically carried out at a temperature of 70°C to 90°C for 1h to 3h.
10. The method for preparing a mulberry branch composite phase change material capable of achieving self-regulating thermal management function according to claim 1, characterized in that The drying in step 2 is specifically carried out at a temperature of 50° C. to 70° C. for 10 h to 20 h.